53 Implementation of a Developmental Outreach Clinic housed within a Family Health Team - preliminary findings in building a shared care model for children and youth with mental health and developmental disorders. (19th August 2020) - Young, Elizabeth; Goldfarb, Rachel; Green, Laurie; Hollamby, Kathleen; Weyman, Karen; Jackson, Linda; Milligan, Karen
Abstract: Background: At our inner city hospital, we developed a shared care model between family health teams (FHTs), pediatricians and developmental pediatricians to care for children with mental health and developmental disorders. In phase one of our study, 84 FHT members participated in focus groups to inform the development of our clinic. Family physicians described their role as "referral agent", "long term supporter" and "healthcare coordinator". They expressed the desire to "learn" and "do more", but noted barriers to providing care, including limited training, lack of service knowledge, limited communication, and cumbersome access to mental health and dual diagnosis services. Phase One was completed and accepted for publication. Phase Two describes the implementation of our clinic using a mixed methods approach and report preliminary findings. Objectives: To evaluate the first two years of implementation of the developmental clinic housed within a family health team (FHT) an obtain feedback from members of the shared care model. Design/Methods: Mixed methods were used including chart review of all patients referred to the clinic and semi structured interviews with primary care physicians, pediatricians and developmental pediatricians regarding their roles in managing children with developmental and mental health disorders, as well as use and impact of the developmental clinic. Results: A total of 115 charts were reviewed between Feb 2016 and Jan 2018. Of all patients seen, 34% were female 64% male and 2% transgender. Ages ranged from 1-17 years. Eighty-one percent had an existing diagnosis and were referred for re-assessment while 43% received a new diagnosis: ASD (72%), ADHD (11%), GDD (11%), learning disorder (3%), Anxiety (1%), Other (1%). There was an 8% no show rate. Providers endorsed improved communication through use of a shared EMR for documentation and messaging, and improved service knowledge through availability of a pediatric service navigator who also used EMR to document service and funding applications. Longer term follow up, namely the roles and responsibilities of pediatrics vs. developmental pediatrics vs. primary care remained unclear. Conclusion: Implementation of the shared care model for this population with primary care is feasible, and does address some stated barriers to care, including improved communication, increased service knowledge, and provision of reassessments. Further areas to develop include clarifying the roles and responsibilities of the different healthcare providers of children with mental health and developmental disorders, and determining what is needed for long-term follow up and transitional care.